Paesaggio, territorio e pianificazione in tre diverse città segnate dalla presenza dell’acqua: Santiago de Compostela, Lione e Mazara Del Vallo a confronto - Boatti, Antonello (Ri-Vista. Research for landscape architecture, 2015)
Identify the means by which water can deeply mark shape, life, management and use of a town. From this point, move and think about policies, plans and projects, which assume as key targets landscape enhancing. These are main topics which inform and are emphasises by this contribution. It is, also, a trip through places, projects and processes, even different between them, offered to the reader. Santiago de Compostela, Lione and Mazara del Vallo become, by this way, the places where to identify the tamed river, the core theme of some landscape and the continuous fighting between nature and humans. Starting from these points, outline, tell and target to the planned or not yet planned project choices, the results achieved or aimed to such landscape, its core signs and the urban space become at the same time, the basic point of preservation, renewal, evolution and its reconquest.